Making the tea or making it to the top? How gender stereotypes impact women fundraisers' careers. (1st March 2022) - Dale, Elizabeth J.; Breeze, Beth
Abstract : This article explores gender stereotypes, discrimination and harassment in the fundraising profession and their impact on women's fundraising careers. Using a feminist analysis, we investigate the types of gender-based stereotyping and harassment experienced by women who are members of the United Kingdom professional fundraising membership body, where 75% of female survey respondents reported experiencing stereotyping. Qualitative analysis of 366 respondents' examples of gender-based stereotyping and data from three focus groups demonstrate how the fundraising profession is gendered, its impact on women and what actions need to be taken to tackle visible and unseen barriers that affect women's careers. We conclude by emphasising the necessity for researchers to investigate non-profit and voluntary organisations with a critical orientation that accounts for the ways in which power is reinforced along categories of gender, age, race, class, disability and sexuality in order to realise the full potential of individual employees and the sector.